IMPROVING STUDENTS’ VOCABULARY MASTERY USING QUIZIZZ: AN ACTION RESEARCH AT A JUNIOR HIGH SCHOOL PONTIANAK - Annisa Putri, Rizki; Arif, Abdul; Kusumaningsih, Citra (IKIP PGRI Pontianak, 2024)
The use of digital platforms in education has transformed a traditional learning to a more digital learning. Thus, teachers need to use and integrate technology into their teaching practice. This classroom action research was conducted to find out what happened to the classroom conditions when Quizizz was implemented in the classroom, and in what ways Quizizz could help improve students vocabulary mastery. The research was conducted in a junior high school Pontianak involving 35 students as the research participants. Data were collected through observation, field notes, and vocabulary tests. The quantitative data were analyzed using descriptive statistics, while the qualitative data were analyzed by using three steps, data reduction, data display, and conclusion. The research findings showed that Quizizz resulted in an improvement in students' vocabulary mastery and created more interesting and enthusiastic classroom conditions in the learning process. The findings showed that Quizizz could improve students vocabulary mastery and increased their motivation and enthusiasm to learn vocabulary through Quizizz. The findings reveal the importance of utilizing digital platforms such as Quizizz to support vocabulary mastery and suggest further investigation of its implementation in other aspects of language learning. Keywords: Vocabulary Mastery, Quizizz, Classroom Action Research